Informed Trading of Mutual Funds: Evidence from Fund‐Underwriter Relationships. Issue 1 (20th July 2018) - Hwang, Hyoseok (David)
Abstract: This paper investigates whether the relationship between investment banks and their affiliated funds helps the funds deliver superior performance due to the information advantage or whether it costs the funds due to the conflict of interest. Using firms with class‐action lawsuits, I examine whether underwriter‐affiliated funds can avoid a potential economic loss from the underwriting clients' fraudulent activities. Consistent with the information advantage hypothesis, I find that affiliated funds reduce their stakes in underwritten firms before the disclosure of the firms' misconduct. Additionally, I find that significant selling activity by the affiliated funds can predict the outcome of a potential lawsuit.